Dissolved oxygen responses to tropical cyclones "Wind Pump" on pre-existing cyclonic and anticyclonic eddies in the Bay of Bengal. (September 2019) - Xu, Huabing; Tang, Danling; Liu, Yupeng; Li, Ying
Abstract: This study examines how dissolved oxygen (DO) responds to tropical cyclones (TCs) "Wind Pump" in a pre-existing cyclonic and an anticyclonic eddy over the Bay of Bengal (BoB) based on Argo and satellite data. Both TCs induced DO temporal decreases in the subsurface waters (Deep Depression BOB 04 with a pre-existing cyclonic eddy and cyclonic storm Roanu with a pre-existing anticyclonic eddy) owing mainly to the storm-induced upwelling. The deeper oxycline caused by the pre-existing anticyclonic eddy relieved the storm-induced shallow of oxycline during Roanu. On the contrary, the pre-existing cyclonic eddy shoaled the oxycline, intensifying the storm-induced shallow of oxycline during BOB 04. Furthermore, the pre-existing cyclonic eddy induced a long time of DO decrease after BOB 04. This study suggests that the subsurface DO concentrations in the BoB are affected mainly by storm-induced physical processes, and the mesoscale eddies also play an important role. Highlights: The intense storm-induced upwelling caused the DO decrease in the subsurface layers. With a pre-existing cyclonic eddy, storm led to a much shallower oxycline and a long time of DO decrease. The physical processes played a more important role than the biological processes in the DO distributions under the influence of storms.